COVID-19 pandemic response by India and future directions - Suraj Kapoor (Wolters Kluwer Medknow Publications, 2022)
Introduction: It has been more than a year since COVID-19 was declared Pandemic by WHO on 11 March 20. India with the initial slow rise of cases had a peak of cases at around September 20 followed by a gradual fall in the number of new cases and faced the second wave with the rising number of cases from March 21 to July 21. There is limited literature examining the pandemic response in India considering policies adopted, economic factors, health-care capacity factors of selected states influencing the variation of the spread of infection in various states. Hence, this study is conducted to understand COVID response, policies adopted by India, and lessons learned. Materials and Methods: This is a descriptive study conducted across the country covering important states covering the period from January 2020 to September 2021. States were selected based on high caseload, high test positivity ratio. Data for the study are compiled from the health bulletins, official handles of health ministries, WHO, World bank, Worldometer, John Hopkins University Centre for Science and Engineering, NFHS 5, etc., Results: On comparing key epidemiological indicators of selected states, Maharashtra has the largest number of cases with the highest Case fatality rate (CFR). Kerala has the second-highest cases among selected states but with the least CFR. On comparing key sociodemographic factors, Kerala has a maximum literacy rate and elderly population, while Delhi has maximum Population density. Despite having maximum risk factors such as the prevalence of diabetes, obesity, and hypertension, Kerala managed to have the least CFR. The reason may be due to the robust surveillance system, high literacy rate, and good doctor-patient ratio comparing other states. Maharashtra the worst affected state managed to do better in the second wave in respect of oxygen supply and vaccination drive. Conclusion: Full lockdowns and early border closures appeared to lessen the peak of transmission and thus prevent health system overcapacity. However, these measures had an impact on the lives of people as well as the economy of the countries. Addressing vaccination drive issues such as supply chain and manufacturing capacity, focussing on the young and pediatric population as well as focussed cluster containment strategies seems to be the most effective strategy to combat the anticipated third wave.